Gut microbiome and metabolome of sea cucumber (Stichopus ocellatus) as putative markers for monitoring the marine sediment pollution in Pahang, Malaysia - Siew, Shing Wei; Choo, Mei Yen; Marshall, Ian P. G.; Abd Hamid, Hazrulrizawati; Kamal, Shamrulazhar Shamzir; Nielsen, Dennis Sandris; Ahmad, Hajar Fauzan (Elsevier, 2022)
Antibiotic contamination in the marine environment forms an emerging threat to marine ecosystems. This study aimed to compare the gut and coelomic microbiota of Stichopus ocellatus with sediments between two coastal districts of Pahang, which potentially conferring as putative biomarkers for sediment pollution monitoring. The composition of the bacteria communities was determined using 16S rRNA V3-region gene amplicon sequencing, while hybrid whole-genome sequencing was employed to analyze the genome of Vibrio parahaemolyticus. The trace elements and antibiotic compositions were access using high throughput spectrometry. The alpha- and beta-diversity of bacteria in gut and sediment samples from Kuantan differed substantially within (p-value = 0.017604) and between samples (p-value <0.007), respectively. Vibrio genera predominated in Kuantan samples, while Flavobacterium and Synechococcus_E genera predominated in Pekan samples. Vibrio parahaemolyticus revealed the presence of tet (35) and blaCARB-33 genes that conceived resistance towards tetracycline and beta-lactam antibiotics, respectively, which were detected in sediment and gut samples.